Advancements in Electric Machines - Gieras, J. F. (Power Systems, 2008)
This book discusses the stateof-the art of electric machines, associated components and contemporary trends of their development. Novel electric machines considered in this book have been limited to rotary electric machines. Linear electric machines and linear actuators have not been included. This volume has three main objectives: Firstly, to promote electrical machines as the most popular machines of everyday life and increase awareness in this area; Secondly, to stimulate innovations in electrical machines and electromechanical drives; Thirdly, to help educators revitalize Power Engineering curricula and change research strategy towards what industry and mankind needs.